1991
DOI: 10.1111/j.1095-8649.1991.tb04378.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oral administration of 3,5,3′‐triiodo‐thyronine on growth, digestion, food conversion and metabolism in the underyearling red sea bream, Chrysophrys major (Temminck & Schlegel)

Abstract: The effect of inclusion of 3,5,3'-triiodo-~-thyronine (T,) in the diet was examined in underyearling red sea bream Chrysophrys major (Temminck 8c Schlegel). The treatment brought about increases in growth rate, appetite, food conversion efficiency and activities of intestinal enzymes including leucine nitroanilidase, alkaline phosphatase, y-glutamyltransferas, a-amylase and disaccharidase. There were no changes in the muscle content of water, protein, lipid and glycogen. Liver glycogen content was elevated, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 41 publications
4
22
0
Order By: Relevance
“…Perhaps thyroid hormones exert similar actions on the gut of teleosts also. Woo et al (1991) observed increased appetite and food consumption efficiency (FCE) as a result of higher intestinal enzyme activity in underyearlings of red sea bream, Chrysophyrys major after oral administration of T 3 . Better FCR following T 4 administration has also been reported in C. carpio (Kumar et al 1991) andC.…”
Section: Discussionmentioning
confidence: 93%
“…Perhaps thyroid hormones exert similar actions on the gut of teleosts also. Woo et al (1991) observed increased appetite and food consumption efficiency (FCE) as a result of higher intestinal enzyme activity in underyearlings of red sea bream, Chrysophyrys major after oral administration of T 3 . Better FCR following T 4 administration has also been reported in C. carpio (Kumar et al 1991) andC.…”
Section: Discussionmentioning
confidence: 93%
“…Literature on thyroid hormone supplementation of fish feed has indicated an anabolic effect in some species (Higgs et al 1979;Saunders et al 1985;Woo et al 1991) with no effect in others (Leatherland et al 1987;Gannam and Lovell 1991).…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that thyroid hormones could influence fish growth (Woo et al 1991;Higgs et al 1992) and survival (Brown et al 1989;Reddy and Lam 1992), especially at larvae and juvenile stages. Therefore, investigation of these hormones may provide a greater understanding of the endocrine control of growth in teleost fish (Nankervis et al 2000).…”
Section: Discussionmentioning
confidence: 99%